Friendships among young professionals during the COVID-19 pandemic - Kimari, Lucy Wanjiru (Strathmore University, 2022)
At the beginning of 2020, the world changed with the vast spread of the COVID-19 virus. With it came many devastating effects some of which though not life threatening, were deemed debilitating to the flourishing of the human person. One of the effects, which this dissertation unpacked, was the state of isolation that many were left in and specifically, young professionals living alone and working from home while located in Nairobi City. The study sought to dig deeper into the social sphere of many young people by determining the perceptions young professionals' held on the need for friendship and the impact of these perceptions. The theoretical basis of the study was tied to man’s need to belong as a fundamental social motive as elaborated by Baumeister & Leary in the Belongingness theory together with man’s instinct for communion and relational nature as defined by Martin Buber’s Dialogical Personalism theory. The research study utilized a phenomenological methodology, best understood as a way to clarify concepts in terms of people's original intuitions by seeking meaning from young professionals' experiences and accounts of friendship during the COVID-19 pandemic. Respondents were selected from a range of categories of work experience levels in the Finance field from early-career, associates to mid-career professionals while also taking into account those who lost their jobs during the pandemic. Purposive sampling was employed, utilizing the maximum variation sampling method with a sample size of twelve respondents and the use of in-depth interviews for data collection. The data was interpreted using a five-step method that included describing the phenomena experienced by the respondent, identifying the common themes, reflecting on the themes to determine the “what” of respondents’ conscious experience and the meaning this held for them. Lastly, intuition and reflection was used to abstract the essences or “why” young professionals experienced their friendships or lack thereof, in the manner that they did. The study highlighted that the pandemic led to certain shifts around friendship among young professionals. Some of the notable highlights include the foundational importance of physical presence, the overriding value of quality versus quantity when it came to friends and most importantly, the critical difference that intentionality, mutuality and reciprocity played in maintaining and deepening friendships especially in adverse circumstances such as the COVID-19 pandemic.
Submitted in partial fulfillment of the requirements for the Degree of Master of Arts in Applied Philosophy and Ethics at Strathmore University
Keywords: Friendship; COVID-19; Pandemic; Young professionals; Working from home; I-Thou; I-It; Martin Buber; Baumeister & Leary; Phenomenology